The Influence of Workload, Job Involvement, and Work Environment on Employee Job Satisfaction at the Department of Transportation, Binjai City - Johanes Aste Frans Karo Karo; Muhammad Toyib Daulay (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This research was conducted at the Department of Transportation of Binjai City with the aim of analyzing the partial and simultaneous effects of workload, work engagement, and work environment on employee job satisfaction. The population consisted of 128 permanent employees, and the sampling technique used was a census, resulting in a total sample of 128 respondents. The type of data used was primary data, with secondary data as supporting sources. Data collection techniques included literature review, surveys, and observation. The data analysis methods applied were multiple linear regression, classical assumption tests, and hypothesis testing. The findings reveal that workload, work engagement, and work environment significantly influence employee job satisfaction, both partially and simultaneously, at the Department of Transportation of Binjai City. There is a strong correlation between these variables and job satisfaction. Employee job satisfaction can be explained by workload, work engagement, and work environment by 51.9%, while the remaining 48.1% is influenced by other factors not examined in this study.